Can cardiac shear wave elastography detect the presence of septal scar in patients with left bundle branch block?. (4th February 2022) - Wouters, L; Duchenne, J; Bezy, S; Papangelopoulou, K; Puvrez, A; Klop, B; Voros, G; D"hooge, J; Voigt, JU
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): FWO: Fonds Wetenschappelijk Onderzoek (fund for scientific research Flanders) Background: Cardiac resynchronization therapy (CRT) is an established treatment for heart failure patients with left bundle branch block (LBBB). Regardless, CRT has proven to be less effective in patients with ischemic cardiomyopathy, in particular when the septum is affected. The detection of septal scar prior to CRT implantation could therefore help to improve response rate. However, magnetic resonance imaging (MRI), the gold standard to assess myocardial scar, cannot be used in every patient due to already implanted devices or impaired renal function. Cardiac shear wave elastography (SWE) allows for the non-invasive assessment of myocardial stiffness via the detection of shear waves, for example induced by mitral valve closure (MVC), that travel through the myocardium. Shear wave speed is directly related to tissue stiffness. Recently, SWE has shown to be capable to detect myocardial scar, however this has never been demonstrated in the presence of LBBB. Purpose: To evaluate whether SWE is able to detect the presence of septal scar in patients with LBBB. Methods: We included 34 heart failure patients with LBBB (age: 69 ± 13 y; 56% males) and with ischemic (n = 9) or non-ischemic (n = 25) cardiomyopathy and 9 age-matched healthy volunteers (age: 68 ± 4 y; 66% males) as controls. In order to obtain native ventricular conduction biventricular (BiV) pacing was turned off. All ischemic patients had septal scar only, proven by MRI or scintigraphy. For SWE, left ventricular parasternal long-axis views were acquired with an experimental high frame rate ultrasound scanner (frame rate: 932 ± 32 fps). Shear waves were visualized in M-modes of the septum, colour coded for tissue acceleration. The slope of the shear waves in the M-mode represents their propagation speed (Figure A). Results: Patient characteristics including echocardiographic parameters are shown in Table 1. Shear wave speed after MVC was significantly higher in patients with LBBB with or without septal scar compared to healthy controls (7.9 ± 1.2 m/s vs 4.5 ± 1.1 m/s; p = 0.044; 5.6 ± 1.2 m/s vs 4.5 ± 1.1 m/s: p < 0.001; figure B). This implies that the presence of LBBB alone increases myocardial stiffness. Most importantly, however, shear wave speed was significantly higher in LBBB patients with a septal scar compared to LBBB patients without a septal scar (7.9 ± 1.2 m/s vs 5.6 ± 1.2 m/s; p < 0.001; figure B), indicating that the presence of scar increases myocardial stiffness even more than LBBB alone. Conclusions: LBBB causes a mild but significant increase in shear wave propagation speed in non-ischemic patients compared to controls. The presence of septal scarring leads to an additional and more significant increase. This indicates that SWE is capable of detecting stiffer scarred myocardium even in the presence of LBBB. Therefore, SWE could potentially be used as a novel method to detect septal scarring in LBBB patients before CRT implantation.